2x - 3y = 9 ; 2x + y = 13
Answers
Answered by
41
by subtracting
2x -3y =9
2x +y =13
- - -
0. -4y = - 4
Y = 1
on putting in eqn.
2 x - 3 ×1 = 9
2x = 12
x =6
2x -3y =9
2x +y =13
- - -
0. -4y = - 4
Y = 1
on putting in eqn.
2 x - 3 ×1 = 9
2x = 12
x =6
Answered by
26
hey mate!!!
2x-3y=9--------(1)
(-) 2x+y=13--------(2). (1)-(2)
- - -
–––––––––––·–––
0-4y=-4
y=1
substitute y value In (2)
2x+1=13
x=6
hope the answer helps u :)
2x-3y=9--------(1)
(-) 2x+y=13--------(2). (1)-(2)
- - -
–––––––––––·–––
0-4y=-4
y=1
substitute y value In (2)
2x+1=13
x=6
hope the answer helps u :)
Similar questions